Association of occupational sitting with cardiovascular outcomes and cardiometabolic risk factors: a systematic review with a sex-sensitive/gender-sensitive perspective. Issue 2 (8th February 2022) - Reichel, Kathrin; Prigge, Michaela; Latza, Ute; Kurth, Tobias; Backé, Eva-Maria
Abstract : Objectives: Sedentary behaviour is a modifiable risk factor for cardiovascular health. Although long periods of sedentary behaviour take place at work, evidence of the relationship between such occupational sitting and cardiometabolic health risks remains limited. This systematic review aimed to update the evidence on the associations of occupational sitting with cardiovascular outcomes and cardiometabolic risk factors based on longitudinal studies. Design: Systematic review. Setting: Workplace. Population: Employees aged 18–65 years. Primary and secondary outcomes: Primary outcomes were cardiovascular diseases and cardiometabolic risk markers. The secondary outcome was all-cause mortality. Data sources: Ten databases, including PubMed, Web of Science and CINAHL (search January 2018, updated February 2019). Data extraction and synthesis: Data were screened, extracted and appraised by three independent reviewers following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Results: Studies were markedly heterogeneous in terms of measurement of occupational sitting, cardiometabolic risk factors and cardiovascular morbidity and mortality, so that standards were hardly identifiable and limiting the value of the evidence. The review included 27 high or acceptable quality publications. Of the eight high-quality publications from seven cohorts, three cohort studies found significant associations of occupational sitting with primary outcomes. Additionally, one study described an association with the secondary outcome. Another high-quality publication found an association between occupational sitting and ischaemic heart disease in a subgroup already at risk due to hypertension. For sex/gender analysis, 11 of the 27 high and acceptable quality publications reported sex-stratified results. Five of these found sex differences. Conclusions: Evidence regarding the association of occupational sitting with cardiometabolic health risks was limited because of the lack of standardised measurements for occupational sitting. Occupational sitting combined with an overall sedentary lifestyle was associated with an elevated relative risk for several cardiometabolic outcomes. There is an urgent need for standardised measurements of occupational sitting to facilitate meta-analysis. Sex/gender aspects of this relationship require further investigation.